Evaluation of mitochondria in mouse oocytes following cisplatin exposure - Qiaochu Wang; Karla J. Hutt (BMC, 2021)
Abstract Background Cisplatin is a platinum-based chemotherapeutic that damages genomic DNA leading to cell death. It also damages mitochondrial DNA and induces high levels of mitochondrial reactive oxygen species (mtROS), further sensitising cells to apoptosis. Notably, immature oocytes are particularly vulnerable to cisplatin treatment, a common side effect of which is depletion of the primordial follicle reserve, leading to infertility and early menopause. Cisplatin is known to damage the DNA of oocytes, but the possibility that cisplatin also compromises oocyte survival and quality by damaging mitochondria, has not been investigated. To begin to address this question, neonatal mice were treated with saline or cisplatin (2 mg/kg or 4 mg/kg) and the short and long-term impacts on mitochondria in oocytes were characterised. Results At 6 and 24 h after treatment, mitochondrial localisation, mass and ATP content in immature oocytes were similar between groups. However, TMRM staining intensity, a marker of mitochondrial membrane potential, was decreased in immature oocytes from cisplatin treated mice compared to saline treated controls, consistent with the induction of apoptosis. When mice were super ovulated 5 weeks after exposure, the number of mature oocytes harvested from cisplatin treated mice was significantly lower than controls. Mitochondrial localisation, mass, membrane potential and ATP levels showed no differences between groups. Conclusions These findings suggest that mitochondrial dysfunction may contribute to the depletion of the ovarian reserve caused by cisplatin, but long-term impacts on mitochondria may be minimal as those immature oocytes that survive cisplatin treatment develop into mature oocytes with normal mitochondrial parameters.